2021
DOI: 10.1007/s11356-021-15821-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications

Abstract: The aim of study was access the cobalt and lead contamination in soil, forages and animals. Heavy metal pollution is a matter of prime significance in natural environment. Through food chain toxicity of heavy metals and their bioaccumulation potential are transferred into humans .Higher concentrations of metallic compounds are toxic to living organisms but these are essential to maintain body metabolism. Intake of food crops polluted with heavy metals is chief food chain channel for human exposure. Animals are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…Similar observations were also made byChen et al (2022). Zinc is a micronutrient that both plants and animals require.…”
supporting
confidence: 82%
“…Similar observations were also made byChen et al (2022). Zinc is a micronutrient that both plants and animals require.…”
supporting
confidence: 82%
“…Our results are also corroborated by an earlier study [ 32 ] that reported immobilization of heavy metals with the application of organic manure. The permissible maximum limits reported by [ 24 ] of the trace metals is Cd 3, Co 65, Cr 100, Cu 50, Pb 300, Fe 21000, Mn 2000, and Zn 200 mg kg −1 deposited in soil. All the treated pots showed lower metal concentrations than permissible limits.…”
Section: Resultsmentioning
confidence: 99%
“…It was measured by following the method provided by [ 24 ]. It is used to assess risk to consumer health.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the total hazard index (THI) evaluates the potential risk of adverse health effects from a mixture of chemical constituents in rice. If this ratio is less than 1, the exposed population is unlikely to experience noticeable adverse effects [14][15][16].…”
Section: Risk Assessmentmentioning
confidence: 99%